Salty Wisdom: Exploring Natrum Muriaticum's Marine Origins and its Healing Powers in Homoeopathy Through Doctrine of Signature. - Yaligouda, Jineshwar Annasaheb; Yaligouda, Padmraj Jineshwar (Homoeopathic Heritage, 2026)
Natrum Muriaticum, prepared from sodium chloride, holds a prominent place in Homoeopathy as a deep acting constitutional remedy. This article examines the therapeutic potential of Natrum Muriaticum through the lens of the Doctrine of Signature, which postulates that a substance's natural form, source, and environment reveal clues to its medicinal action. Drawing from its marine origin, the remedy reflects themes of preservation, grief, and emotional retention paralleling the properties of the sea: vast, deep, and holding dissolved minerals. This correlates these symbolic signatures with the clinical picture of Natrum Muriaticum, including its use in chronic grief, headaches, skin conditions, and ailments linked to suppressed emotions. By bridging traditional homoeopathic philosophy with modern materia medica, this article highlights how understanding a remedy's natural source deepens clinical insight and remedy selection. Natrum Muriaticum thus embodies "salty wisdom" healing that arises from the very depths it originates.